Voices from the Margins: Barriers and Facilitators to HPV Self-Sampling Among Structurally Marginalized People with a Cervix in the Greater Toronto Area and Ontario - Mandana Vahabi; Natasha Kithulegoda; Masoomeh Moosapoor; Aisha Lofters; Josephine Pui-Hing Wong; Abdolreza Akbarian; Jenna Hynes (Current Oncology)
Sex workers and formerly incarcerated people with a cervix face significant structural, interpersonal, and emotional barriers to cervical cancer screening, despite being at elevated risk for HPV infection. HPV self-sampling (HPV-SS) is a validated, user-directed method that has the potential to address these barriers, yet it remains excluded from Ontario’s organized screening program. This qualitative study explored the lived experiences of structurally marginalized individuals with a cervix who were offered HPV-SS as part of a mixed-methods pilot in the Greater Toronto Area. Five virtual focus groups were conducted with 34 participants, including both those who used the HPV-SS kit and those who declined it. Using inductive thematic analysis, we identified barriers to traditional screening including fear, stigma, mistrust of healthcare providers, logistical constraints, and a lack of accessible information. HPV-SS was widely described as more acceptable, empowering, and emotionally manageable, offering participants autonomy, privacy, and control over their care. Concerns included swab design, uncertainty about correct use, and unclear follow-up after positive results. Participants offered concrete, community-informed recommendations to improve HPV-SS implementation, including opt-in distribution models, gender-affirming language, and trauma-informed educational materials. The findings highlight the urgent need to integrate HPV-SS into organized screening programs to advance equitable access to cervical cancer prevention for marginalized populations.